Prevalence of Angiographically Significant Left Main Disease at a Tertiary Care Hospital in Karachi; A Large Cardiac Interventional Study - Javaid Ur Rehman, Samiullah, Naveedullah, Javed Khurshed Shaikh, Iftikhar Ahmed, Tariq Ashraf, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the prevalence of significant left main coronary artery disease (Stenosis more than 50%) at NICVD Karachi. Method: We conducted this observational cross-sectional study retrospectively at NICVD Karachi. Our institution analyzed both emergency and elective coronary angiography data from 5th July 2018 to 5th July 2020 for the existence of significant left main coronary artery disease. A study of coronary artery disease only included patients with significant left main coronary artery disease. Approximately 50% stenosis was considered significant left main coronary artery disease. Results: A total of 10,828 patients were selected for the study population, out of the total of 8975 males and 1853 female patients who underwent coronary angiography during our mentioned period at NICVD Karachi, 327 patients (3%) showed significant left main coronary artery disease. 277 patients (83%) were male and 50(17%) were female. About 50% of patients were between the ages of 60 -80 years old Minimum age was 32 years and the maximum age was 95 years. Hypertensive were 5197 (48%) and diabetes was 2480 (22.9%). The maximum number of patients in CCS grade II angina is about 239 (73.0%). Conclusion: High prevalence of disease in the Left major coronary artery is associated with greater mortality and morbidity in our CAD patients.